A cross-linguistic study of certain temporal features of speech in stuttering and nonstuttering children - Oosthuizen, Carol Louise (Department of Psychology, 2023)
Four experiments were performed to measure temporal coarticulatory speech features in the perceptually fluent speech of 120 South African children. The aim was to test, in a limited way, the postulate that stuttering may be essentially a disorder of speech timing. Comparisons were made between English- and Afrikaans-speakers, between younger (mean age 4.1 years) and older (mean age 6. 7 years) children, and between stutterers and nonstop utterers. Experiment one investigated voice onset time (VOT) of word-initial voiced and voiceless bilabial and apical stop plosives in isolated eve nonsense syllables. The VOTs were measured from oscilloscopic displays. Nonparametric statistical treatment identified certain trends in the data. English-speakers used short- and long-lag categories to express voiced and voiceless initial stops respectively. They showed a developmental trend in the direction of lengthening of VOT for voiceless stops. Afrikaans-speakers used two sets of short-lag VOT without aspiration to produce voiced and voiceless stops. Voicing lead occurred randomly as a stylistic variant. The stuttering children demonstrated longer VOTs than did nonstutterers. In addition, English-speaking stutterers failed to lengthen VOT for voiceless stops in the normal manner. This was attributed to difficulty with the physiological demands of long-lag VOT. Afrikaans speakers, who did not have to contend with the long-lag category, clearly distinguished between voiced and voiceless stops by means of VOT. Experiment two dealt with the categorical labelling of nonsense syllables employing the voicing contrast. In younger nonstuttering subjects, English-speakers performed better than did Afrikaans-speakers, owing to the greater number of perceptual cues available to them. All younger subjects needed a lot of training in order to label correctly, whereas older subjects needed little training. English stutterers performed slightly poorer than did nonstutterers, while even older Afrikaans stutterers performed very poorly. It was postulated that stutterers might be dependent on perceptual cues which become redundant for nonstuttering listeners. Afrikaans stutterers were additionally handicapped by the paucity of perceptual cues in their language. In experiments three and four, medial stop closure duration in vev nonsense syllables and medial vowel durations in eve nonsense syllables were measured. English and Afrikaans nonstutterers had longer stop closure durations on voiceless-than stops and in high vowel compared with low vowel environments. A devel6p:nental trend was identified in the direction of differential stop closure lengthening. Medial vowel durations were also lengthened in voiced and voiced sibilant consonant environments. Subjects showed increasing vowel differential durations with age. Stutterers showed the normal trends towards differential medial stop closure and vowel durations but appeared to have a developmental lag in this respect relative to nonstutterers. Since stutterers did not differ from nonstutterers on measures of whole syllable duration or medial VOT it did not appear as if they were simply moving their articulators slowly. Experiments three and four probably tapped neutrally programmed coarticulatory effects, whereas the VOT measure might reflect a lower aerodynamic-neuromuscular level of speech functioning, the voicing feature being primarily involved at both levels. The possibility exists and is strengthened by the results of the categorical labelling task, that a central timing disorder, manifest as a developmental lag, may have been operating in the stuttering subjects.